Utility of optical facial feature and arm movement tracking systems to enable text communication in critically ill patients who cannot otherwise communicate - John Dingley (Burns, 2014)
PURPOSE:Patients recovering from critical illness especially those with critical illness related neuropathy, myopathy, or burns to face, arms and hands are often unable to communicate by writing, speech (due to tracheostomy) or lip reading. This may frustrate both patient and staff. Two low cost movement tracking systems based around a laptop webcam and a laser/optical gaming system sensor were utilised as control inputs for on-screen text creation software and both were evaluated as communication tools in volunteers.METHODS:Two methods were used to control an on-screen cursor to create short sentences via an on-screen keyboard: (i) webcam-based facial feature tracking, (ii) arm movement tracking by laser/camera gaming sensor and modified software. 16 volunteers with simulated tracheostomy and bandaged arms to simulate communication via gross movements of a burned limb, communicated 3 standard messages using each system (total 48 per system) in random sequence.RESULTS:Ten and 13 minor typographical errors occurred with each system respectively, however all messages were comprehensible. Speed of sentence formation ranged from 58 to 120s with the facial feature tracking system, and 60-160s with the arm movement tracking system. The average speed of sentence formation was 81s (range 58-120) and 104s (range 60-160) for facial feature and arm tracking systems respectively, (P<0.001, 2-tailed independent sample t-test).CONCLUSION:Both devices may be potentially useful communication aids in patients in general and burns critical care units who cannot communicate by conventional means, due to the nature of their injuries.